The Assistance to Participate Scale to measure play and leisure support for children with developmental disability: update following Rasch analysis. Issue 4 (13th June 2013) - Bourke‐Taylor, H.; Pallant, J. F.
Abstract Background The Assistance to Participate Scale (APS) was designed to measure the primary carer's estimate of the amount of assistance that their school‐aged child with a disability requires to participate in play and leisure activities. Previous research suggests that the 8‐item APS has good internal consistency. The construct validity of the scale is supported by strong correlations with instruments measuring similar constructs and discrimination between groups of children with developmental disability, based on extent of need for caregiver assistance. Aim The aim of this current study was to undertake further evaluation of the psychometric properties of the APS using Rasch analysis. Method Rasch analysis was conducted using the RUMM2030 program to assess the APS items in terms of their overall fit to the Rasch model, individual item fit, response format, targeting and dimensionality. Results Rasch analysis showed good fit to the model, with no misfitting items and good internal consistency (PSI = 0.85). There was no differential item functioning across mothers' age, education level or child's age. Dimensionality testing supported the combination of all items to create a total score. Most items showed disordered thresholds, suggesting some inconsistencies in the way respondents used the response scale options. Conclusions The APS has been subjected to substantial psychometric testing during development and evaluation, revealing a sound, brief and easy‐to‐use scale. The APS has a number of potential clinical and research uses measuring the amount of additional assistance that children require from their primary care giver to participate in play activities.